Analisis Sitem Informasi Akuntansi Penggajian dan Pengupahan Dalam Meningkatkan Pengendalian Intern Pada PT. POS Indonesia (Persero) Kantor Cabang Binjai 20700 - Andi Putri, Fahresya Nuradinda; Marliyah, Marliyah; Lubis, Arnida Wahyuni (Journal of Computer Science and Information System(JCoInS), 2024)
This research aims to analyze the payroll and wage accounting information system that has been implemented by PT. Pos Indonesia (Persero) Binjai Branch and analyzing the payroll accounting information system to improve internal control. This type of research is qualitative research, which uses a qualitative descriptive analysis approach, data collection techniques using interview method analysis, which focuses on the Payroll accounting information system and Internal Control System at PT. Pos Indonesia (Persero) Binjai Branch. Data analysis in research begins by analyzing related functions, supporting documents, accounting records used, procedural networks and the effectiveness of internal control. The research results found evidence that the payroll system at PT. Pos Indonesia (Persero) Binjai Branch has been running quite effectively but there are still several shortcomings, where every time there is a change in salary and wages there is no provision from the management for changes in salary and wages, that is without showing a decision letter for changes to employee salaries and wages so that fraud can occur, Fair practices applied to support internal control are by transferring employees' basic salaries to each employee's account by the director and making duplicate salary slips, and employee negligence in absent fingerprints or barcodes, as well as having duplicate duties in the payroll accounting information system and Remuneration.